2015
DOI: 10.1038/srep13982
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of dendritic cells and T lymphocytes for the therapeutic effect of Dangguiliuhuang decoction to autoimmune diabetes

Abstract: In traditional Chinese medicine (TCM), Dangguiliuhuang decoction (DGLHD) is an effective treatment of autoimmune diabetes. Here, we studied potential anti-diabetic mechanisms of DGLHD in a non-obese diabetic (NOD) mouse model. In vitro, DGLHD and individual active ingredients enhanced glucose uptake in HepG2 cells, inhibited T lymphocyte proliferation, and suppressed dendritic cells (DCs) function. In vivo, DGLHD significantly inhibited insulitis, delayed the onset and development of diabetes, promoted insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…In TCM, combinatory therapeutic strategies based on patient symptoms and characteristics are often adopted to treat several diseases [ 14 ]. The Chinese herb formulae consist of several types of medicinal herbs or minerals, and multiple components could act on multiple targets and exert synergistic therapeutic efficacies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In TCM, combinatory therapeutic strategies based on patient symptoms and characteristics are often adopted to treat several diseases [ 14 ]. The Chinese herb formulae consist of several types of medicinal herbs or minerals, and multiple components could act on multiple targets and exert synergistic therapeutic efficacies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the liver is an important organ in the regulation of lipids and glucose metabolism and that ASP is a liver-targeting natural product, we speculated that ASP might have beneficial effects on metabolic diseases. Several studies have demonstrated that ASP and Angelica sinensis exerts appreciable hypoglycemic and hypolipidemic effects in diabetic rats 14 18 . Based on these studies, we evaluated the beneficial effects of ASP in a long-term HFD treatment-induced mouse model of fatty liver, hyperglycemia, hyperlipidemia, insulin resistance and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The formulae combined plant species and minerals that were prescribed based on clinical experience. Multiple components of the formula could interact with multiple targets and exert synergistic therapeutic efficacies [ 12 , 13 ]. The optimized formula of XFHM (once named Lijie capsule) used in this study is comprised of 12 different herb.…”
Section: Introductionmentioning
confidence: 99%